Survival benefit of hepatic resection versus transarterial chemoembolization for hepatocellular carcinoma with portal vein tumor thrombus: a systematic review and meta-analysis - Xiu-Ping Zhang; Kang Wang; Nan Li; Cheng-Qian Zhong; Xu-Biao Wei; Yu-Qiang Cheng; Yu-Zhen Gao; Han Wang; Shu-Qun Cheng (BMC Cancer, 2017)
Abstract Background No consensus treatment has been reached for hepatocellular carcinoma (HCC) with portal vein tumor thrombus (PVTT). Hepatic resection (HR) and transarterial chemoembolization (TACE) have been recommended as effective options, but which is better remains unclear. This meta-analysis is to compare the effectiveness of HR and TACE for HCC with PVTT patients. Methods The PubMed, EMBASE, Cochrane Library, VIP, Wan Fang, and Sino Med databases were systematically searched for comparing HR and TACE treating PVTT. Results Twelve retrospective studies with 3129 patients were included. A meta-analysis of 11 studies suggested that the 1-, 2-, 3-, and 5-year overall survival (OS) rates (OR = 0.48, 95% CI = 0.41–0.57, I2 = 37%, P < 0.00001; OR = 0.21, 95% CI = 0.12–0.38, I2 = 43%, P < 0.00001; OR = 0.35, 95% CI = 0.28–0.44, I2 = 53%, P < 0.00001; OR = 0.28, 95% CI = 0.14–0.54, I2 = 72%, P = 0.0001, respectively) favored HR over TACE. In a subgroup analysis, HR had better 1-, 2-,3, 5-year OS for type I PVTT (OR = 0.33, 95% CI = 0.17–0.64, I2 = 20%, P = 0.001; OR = 0.32, 95% CI = 0.16–0.63, I2 = 0%, P = 0.001; OR = 0.18, 95% CI = 0.09–0.36, I2 = 0%, P < 0.00001; OR = 0.07, 95% CI = 0.01–0.32, I2 = 0%, P = 0.0006, respectively) and better 1-, 3-, and 5-year OS for type II PVTT (OR = 0.37, 95% CI = 0.20–0.70, I2 = 59%, P = 0.002; OR = 0.22, 95% CI = 0.13–0.39, I2 = 0%, P < 0.00001; OR = 0.16; 95% CI = 0.03–0.91; I2 = 51%, P = 0.04, respectively). There was no difference in 1-, 3-, or 5-year OS between HR and TACE for type III PVTT (OR = 0.86, 95% CI = 0.61–1.21, I2 = 0%, P = 0.39; OR = 0.83, 95% CI = 0.42–1.64, I2 = 0%, P = 0.59; OR = 0.59, 95% CI = 0.06–-6.04, I2 = 65%, P = 0.66, respectively). Conclusions HR may lead to longer OS for some selected HCC patients with PVTT than TACE, especially for type I or II PVTT, with less difference being observed for type III or IV PVTT.